Evaluating Perceived Service Quality, Perceived Playfulness, and Gratification towards User’s Attitude of Mobile Instant Messaging Application - Prima Ayundyayasti; Arum Febriyanti Ciptaningtias (Bina Nusantara University, 2021)
The research aimed to understand the behavior and adoption of mobile instant messaging (MIM) usage. By applying perceived service quality towards perceived playfulness and gratification model, the research investigated the factors related to MIM usage. Two most popular MIM applications used in Semarang, Indonesia, namely WhatsApp and LINE were targeted. After testing and validating the reliability and validity, questionnaires were distributed to university students and employees in Semarang, Indonesia whom already used MIM applications. The measurement of the constructs in the proposed model was confirmed with confirmatory factor analysis (CFA) to test the consistency of question items within each construct. The outcomes of the questionnaire were tested through structural equation modeling (SEM) to test whether the proposed constructs are confirmed to the designated model. Path coefficient and fit indices of the proposed conceptual model were also used to measure the possible relations between variables. The results show positive influences of perceived service quality, perceived playfulness, and gratification towards user’s attitude.